Cytotoxicity and antibacterial activity of bleached turmeric hydro-alcoholic extract versus sodium hypochlorite as an endodontic irrigant: in vitro study - Salem, Walaa Hassan; Moussa, Taheya Ahmed; Abouraya, Nehal Lofty Abou (Brazilian Dental Science, 2022)
Objective: To evaluate the cytotoxicity and antibacterial effect of bleached turmeric hydro-alcoholic extract compared to sodium hypochlorite as an endodontic irrigant. Material and Methods: Cytotoxicity was evaluated on human skin fibroblasts using MTT assay. The irrigants were tested at 1, 5- and 15-minutes time intervals. After contact time, MTT solution was added and well plates were incubated. After the incubation period, optical density was read and correlated with cell viability percent. Antibacterial efficiency was evaluated using direct contact test. Each endodontic irrigant was added to fresh Enterococcus faecalis suspension and brain heart infusion media then incubated for 48 hours. After incubation period, optical density readings were obtained and read by ELISA reader at 620 nm. Results: Results of cytotoxicity test revealed that bleached turmeric extract had significant higher cell viability percent than Sodium hypochlorite (NaOCl) at all time intervals (p<0.001). However, in the intervention group, cell viability percent significantly decreased over time. Results of antibacterial test showed bacterial inhibition by both groups with non-significant difference between the two tested groups (p<0.05). Conclusion: Bleached turmeric hydro-alcoholic extract can represent an herbal alternative endodontic irrigant to avoid the undesirable toxic effects of NaOCl due to its less cytotoxicity and prominent antibacterial effect against Enterococcus faecalis. KEYWORDS Antibacterial effect; Bleached turmeric; Cytotoxicity; Endodontic irrigantion; Sodium hypochlorite.